ANALISIS EFEKTIFITAS DAN KONTRIBUSI PAJAK BUMI DAN BANGUNAN PEDESAAN DAN PERKOTAAN (PBB-P2) TERHADAP PENINGKATAN PENERIMAAN PENDAPATAN ASLI DAERAH DI KABUPATEN MINAHASA SELATAN DAN KOTA MANADO - Lintong, Felia; Sabijono, Harijanto; Kalalo, Meily Y. B. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Basically Tax is a levy or a contribution to the state and also the main source of income from taxes. Law no. 12 Year 1985 is the basis of collecting Land and Building Tax, while Land Tax and Rural and Urban Buildings are potential for the revenue of local origin. The purpose of this study was to determine the effectiveness and contribution of land taxes and rural and urban buildings in South Minahasa District and Manado City. The research used is a qualitative descriptive method. The research data is collected by direct interviews with the parties concerned and by literature study. The results showed that the effectiveness of tax revenue earth and rural and urban buildings South Minahasa District 88.12% (quite effective), and Manado City 95.52% (effective). The contribution of the land tax and rural and urban buildings to the local revenue of South Minahasa Regency is 4.55% (very less), and Manado City is 9.46% (very less).Keywords: PBB-P2, income, effectiveness, and contribution